The impact of smartphone addiction on Chinese university students? Physical activity: Exploring the role of motivation and self-efficacy - Lin, Bo (Dove Medical Press Ltd, 2022)
Background: Previous studies showed that smartphone addiction (SA) can lead to reduced physical activity (PA), but only a few studies have explored the impact of SA from psychological perspective closely related to PA. This study aimed to examine the extrinsic and partial psychological factors leading to decrease in PA using structural equation modelling analysis.Methods: We conducted an online survey on 628 males and 1159 female students from 10 universities in Henan Province, China, through a questionnaire survey application ``Questionnaire Star''. This study used three models to test the mediating effects of three types of motives (intrinsic motives, body-related motives, and social motives) and self-efficacy, respectively, in the relationship between smartphone addiction and physical activities.Results: Our result confirmed that smartphone addiction leads to lower physical activities. Secondly, self-efficacy mediates smart -phone addiction and physical activities, but the mediating effect of all three types of motivation is not significant. Thirdly, smartphone addiction did not affect intrinsic motivation and body-related motivation, but positively affects social motivation. Finally, as the motivation type changes from internal to external, the mediating effect of self-efficacy becomes stronger.Conclusion: This study showed that smartphone addiction lead to increase social motivation and decreased self-efficacy, and is a potential barrier to personal participation in physical activities. Our findings provide a new perspective for future design physical activities interventions in China and worldwide especially among university students where smartphone addiction is a problem.